2008
DOI: 10.1093/bioinformatics/btn096
|View full text |Cite
|
Sign up to set email alerts
|

An analytical pipeline for genomic representations used for cytosine methylation studies

Abstract: Representations of the genome can be generated by the selection of a subpopulation of restriction fragments using ligation-mediated PCR. Such representations form the basis for a number of high-throughput assays, including the HELP assay to study cytosine methylation. We find that HELP data analysis is complicated not only by PCR amplification heterogeneity but also by a complex and variable distribution of cytosine methylation. To address this, we created an analytical pipeline and novel normalization approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 32 publications
1
62
0
Order By: Relevance
“…44 This genomic methylation array of 720,001 probes was designed to focus on CpG islands near transcription start sites. The Pearson Correlation test 45 showed that the majority of methylation intensity signals was similar in all cell lines (Fig. S2A).…”
Section: Dna Demethylating Agent 5-aza-deoxycytidine (5-aza-dc) Revermentioning
confidence: 95%
“…44 This genomic methylation array of 720,001 probes was designed to focus on CpG islands near transcription start sites. The Pearson Correlation test 45 showed that the majority of methylation intensity signals was similar in all cell lines (Fig. S2A).…”
Section: Dna Demethylating Agent 5-aza-deoxycytidine (5-aza-dc) Revermentioning
confidence: 95%
“…Freshly isolated islets were used for all studies. To remove the confounding factors contributed by even slight differences in purity between islet preparations, we use quantitative RT-PCR to determine the relative levels of endocrine (insulin) and exocrine (amylase) gene expression levels in each sample as previously described (15). This approach allowed us to determine that there was negligible exocrine tissue contamination of isolated pancreatic islets.…”
Section: Methodsmentioning
confidence: 99%
“…Microarray Data Analysis-Microarray data were pre-processed and subject to quality control and quantile normalization as we have previously described (15). HpaII/MspI ratio values were then compared between groups for all loci throughout the rat genome using a standard t test for IUGR (n Ļ­ 4) and controls (n Ļ­ 4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 720K Roche-NimbleGen custom array capturing 117 521 HpaII fragments was used to assay CpG islands, CpG island shores and reference sequence promoters. Quality control of arrays included assessment of MspI and HpaII intensity distribution and spatial uniformity of the Cy3 and Cy5 signals (49). For all queried HpaII fragments, intensities were processed to determine the Q-centered (Qcent) ratio and the log 2 multi-sample, quantile-normalized unmethylated/methylated (HpaII/MspI) ratio.…”
Section: Help Assaymentioning
confidence: 99%